Smart drug delivery systems to overcome drug resistance in cancer immunotherapy - Wenzhe Yi; Dan Yan; Dangge Wang; Yaping Li (Cancer Biology & Medicine, 2023)
Cancer immunotherapy, a therapeutic approach that inhibits tumors by activating or strengthening anti-tumor immunity, is currently an important clinical strategy for cancer treatment; however, tumors can develop drug resistance to immune surveillance, resulting in poor response rates and low therapeutic efficacy. In addition, changes in genes and signaling pathways in tumor cells prevent susceptibility to immunotherapeutic agents. Furthermore, tumors create an immunosuppressive microenvironment via immunosuppressive cells and secrete molecules that hinder immune cell and immune modulator infiltration or induce immune cell malfunction. To address these challenges, smart drug delivery systems (SDDSs) have been developed to overcome tumor cell resistance to immunomodulators, restore or boost immune cell activity, and magnify immune responses. To combat resistance to small molecules and monoclonal antibodies, SDDSs are used to co-deliver numerous therapeutic agents to tumor cells or immunosuppressive cells, thus increasing the drug concentration at the target site and improving efficacy. Herein, we discuss how SDDSs overcome drug resistance during cancer immunotherapy, with a focus on recent SDDS advances in thwarting drug resistance in immunotherapy by combining immunogenic cell death with immunotherapy and reversing the tumor immunosuppressive microenvironment. SDDSs that modulate the interferon signaling pathway and improve the efficacy of cell therapies are also presented. Finally, we discuss potential future SDDS perspectives in overcoming drug resistance in cancer immunotherapy. We believe that this review will contribute to the rational design of SDDSs and development of novel techniques to overcome immunotherapy resistance.